PENERAPAN KOMPRES HANGAT DI DAERAH AXILLA PADA ANAK USIA PRASEKOLAH 3-6 TAHUN DENGAN THYPOID YANG MENGALAMI MASALAH HIPERTERMI DI RUANG MELATI RUMAH SAKIT TK.II DUSTIRA CIMAHI TANGGAL 01-03 MEI 2024 - Sandi; Octaviani, Oky (Yayasan Putra Sukamanah Sejahtera, 2024)
Typhoid is an infectious disease caused by Salmonella Thypi and can be transmitted through various ways, namely Food, Fingers, Flies, Feces, and Vomitus. Typhoid is a health problem for the world community, the incidence of typhoid in Indonesia is 70% in preschool-age children. Hyperthermia is a condition in which individuals experience an increase in body temperature >37.5°C. Warm compress therapy in the axsilla is one action to reduce fever. Warm compresses are carried out 3 days for 15 minutes. The results of a case study of applying warm compresses in the axsilla showed that body temperature improved, skin temperature improved with an average decrease in fever of 1°C. The application of warm compresses in the axsilla that is carried out shows the achievement of the target indicators that have been set and a decrease in body temperature. It can be concluded that the application of warm compresses in the axsilla is effective for reducing typhoid fever in preschool-aged children. Thus the author provides advice for the public to understand the application of warm compresses in the axsilla when the child has a fever.